(untitled) (Al-Aasar, 2025)
The study investigates how English is used in combination with Urdu in Pakistani social media discourse, focusing particularly on the patterns of code-mixing and the pragmatic functions it serves. With the rise of platforms like Facebook, WhatsApp, and Instagram, young Pakistani users increasingly engage in bilingual communication. The research explores how and why English is mixed with Urdu in these digital spaces, and what social, emotional, and cultural purposes it fulfills. Using a qualitative methodology, the study collected 40 social media posts and conducted 20 informal interviews with undergraduate students aged 18–25. Thematic analysis revealed that English is not used randomly but serves specific functions: expressing emotions politely, constructing modern identity, creating humor, and sharing cultural or religious values. The findings show that code-mixing is largely unconscious and reflects bilingual fluency rather than language confusion. The study concludes that Pakistani youth use English pragmatically and creatively in social media contexts, shaping a localized and functional variety of digital discourse. The results contribute to the field of World Englishes by highlighting how English is adapted and domesticated in online environments. Recommendations are provided for educators and curriculum designers to better understand and embrace students’ real-world language practices.